The end of Irish history?: Reflections on the Celtic Tiger - Coulter, Colin; Coleman, Steve (Manchester University Press, 2003)
Ireland appears to be in the throes of a remarkable process of social change. Over the last decade, the apparently inescapable status of the twenty-six counties as an economic casualty has been dramatically reversed. In recent years, it has become commonplace for the Irish Republic to register formal rates of economic growth that are the envy of every other western European state. The purpose of this exciting new book is to systematically scrutinise the interpretations and prescriptions that inform the deceptively simple metaphor of the 'Celtic Tiger'. The standpoint of the book is that a more critical approach to the course of development being followed by the Republic is urgently required. The essays collected here set out to expose the fallacies that drive the fashionable rhetoris of Tigerhood. Four of these fallacies - that Ireland has cast off the chains of economic dependency, that everyone is benefiting from the economic recovery, that personal freedom and liberty are at an unprecedented level for all citizens, and that Ireland is also experiencing a period of strong cultural renaissance - are vigorously challenged. An esteemed list of contributors deal with issues such as immigration, women's issues, globalisation, and changing economic and social conditions. This book will be essential reading for all students of modern Ireland.